Penerapan Electronic Governance Terhadap Pelayanan di Mall Pelayanan Publik Berkah Dayanan Kabupaten Bolaang Mongondow Selatan - Jasin Saleh, Ruslan Mohamad; Rahmisyari; Musafir (Jurnal Penelitian Multidisiplin Ilmu, 2024)
This research aims to examine more deeply the implementation of e-government in the Blessing of Dayanan Public Service Mall of South Bolaang Mongondow Regency and to understand the extent to which this innovation has improved the quality of public services and what are the challenges faced in the implementation process. The research method used is qualitative with a descriptive approach. Data collection in this study was carried out through observation, interviews and documentation on government employees, stakeholders and service user communities. The results of this study show that e-government policy has been established to improve the quality of public services, but its implementation has not been optimal. In terms of effectiveness, digital services are still constrained by technical disruptions and the low digital literacy of the community. The efficiency expected through service digitization has also not been achieved due to limited technological infrastructure and inadequate internet connectivity. Service transparency shows potential for improvement although public trust in digital systems is still low. The main obstacles include suboptimal availability of human resources, resistance to technological change within the organization as well as limited technological infrastructure and budget. In addition, the community's digital literacy gap is a significant obstacle in utilizing technology-based services.The findings contribute to the development of more adaptive policies to support the success of e-government in South Bolaang Mongondow Regency.